The degree of Using social media to improve Alqunfudah University College students' engagement and achievement from faculties' perspectives and its barriers - Ali Alzebidi (Umm Al-Qura University, 2022)
This qualitative study examined the degree of using social media to improve students' engagement and achievement at Alqunfudah University College based on the faculty members' perspectives and its potential barriers. 15 male and 15 female faculty members from this university college were interviewed to highlight the use and barriers of social media for academic purposes such as Twitter, Instagram, Facebook, and YouTube. The results of this study showed that faculty members at Alqunfudah University College perceived that the use of social media as a part of educational curriculum planning improve students' engagement and achievement from their perspectives. Potential Barriers to the use of social media into the academic course planning of faculty members at this institution were highlighted as the lack of technology environmental infrastructure as the most perceived barrier to its use. Also, the limit of attitude toward how to incorporate social media platforms into their curriculums operated. In addition, Online learning issues was also a barrier that encounter faculty members regarding implementing such tools as a final barrier.